2022
DOI: 10.1002/vms3.725
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of client complaints and their effects on veterinary support staff

Abstract: Background: Veterinarians and support staff have been reporting the negative mental health effects from client complaints (CC). A previous study was performed evaluating these effects in veterinarians however no such study has been performed on veterinary support staff (VSS). Objectiv:The purpose of this study was to investigate the frequency and effects of CCs on VSS. Methods:A cross sectional anonymous survey using a web-based questionnaire was created evaluating the frequency, type, and effects from CC. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…In some cases, the experience of client complaints precipitated a change in role, leading veterinarians to alter their career focus or practice type. A similar trend was also reported in a study examining the impact of complaints on veterinary support staff, where 26.5 per cent of respondents reported considering a career change following client complaints 9 . This is a particular concern given that there is currently a shortage of veterinary staff within the UK 10…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In some cases, the experience of client complaints precipitated a change in role, leading veterinarians to alter their career focus or practice type. A similar trend was also reported in a study examining the impact of complaints on veterinary support staff, where 26.5 per cent of respondents reported considering a career change following client complaints 9 . This is a particular concern given that there is currently a shortage of veterinary staff within the UK 10…”
supporting
confidence: 69%
“…A similar trend was also reported in a study examining the impact of complaints on veterinary support staff, where 26.5 per cent of respondents reported considering a career change following client complaints. 9 This is a particular concern given…”
mentioning
confidence: 99%
“…On the other hand, the modes of communication mean the process of informed consent, such as explanations and information. Effective modes of communication might have become the standard operation procedure (SOP) and online-friendly tools to help clients get information during these years, as previously reported [ 26 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The legal system does not provide an option to treat complaints of a less heavy character, and/or rooted in the owner's frustration, through a different complaint route. The "unfound" ruling can only be made after a full disciplinary procedure, which plays a major role in the veterinarian's well-being and job satisfaction (4)(5)(6). It seems safe to conclude that the current method of working could be adapted.…”
Section: Discussionmentioning
confidence: 99%
“…Owners rarely realize the effect of their complaints. CCs have a huge impact on veterinarians and their co-workers (4)(5)(6). Recent studies investigating the effect of complaints in both human and veterinarian medicine have shown that complaints contribute to psychological distress such as depression, burnout, anxiety, and even suicidal ideation (7,8), and health problems such as cardiovascular disease, .…”
Section: Introductionmentioning
confidence: 99%